"Propuesta de un sistema de gestión de calidad basada en la norma internacional ISO 9001:2015 en la empresa Jataring CIA. lTDA. - Buste Sánchez, Lisbeth Marianela (2019)
The main objective of this work is to develop a proposal for a Quality Management System based on the international standard ISO 9001: 2015, the company is dedicated to the Manufacture and assembly of metal structures for the Agro industrial sector, in order to satisfy better the needs of all clients both national and international. A quality management system based on the international standards ISO 9001: 2015 was designed, in the company JATARIG CIA LTDA of the city of Quevedo, the investigation process begins with a diagnosis of the current situation of the company according to the requirements of the standards. The diagnosis of the current situation of the company showed that the poor management of the processes and the lack of standardization of the work procedure and the lack of control through indicators and through an Ishikawa diagram to analyze the causes and effects. A manual of QMS was carried out, with the mandatory fields, the procedure manual and the formats of the records required by the international standard, in order to continuously improve the overall performance of the company and thus achieve success. Keywords: Process Management System - Quality, Improvement continues.